Proton-coupled electron-transfer processes in ultrafast time domain: evidence for effects of hydrogen-bond stabilization on photoinduced electron transfer - Dey, Ananta; Dana, Jayanta; Aute, Sunil; Maity, Partha; Das, Amitava; Ghosh, Hirendra N. (Chemistry-A European Journal, 2017)
The proton-coupled electron-transfer (PCET) reaction is investigated for a newly synthesized imidazoleanthraquinone biomimetic model with a photoactive RuIIpolypyridyl moiety that is covalently coupled to the imidazole fragment. Intramolecular H-bonding interactions between imidazole and anthraquinone moieties favor the PCET process; this can be correlated to an appreciable positive shift in the one-electron reduction potential of the coordinated anthraquinone moiety functionalized with the imidazole fragment. This can also be attributed to the low luminescence quantum yield of the RuII-polypyridyl complex used. The dynamics of the intramolecular electron-transfer (ET) and PCET processes are studied by using femtosecond transient absorption spectroscopy. The steady- state spectroscopic studies and the results of the time- resolved absorption studies confirm that H- bonded water molecules play a major role in both ET and PCET dynamics as a proton relay in the excited state. The electron- transfer process is followed by a change in the H- bonding equilibrium between AQ and imidazole in acetonitrile solvent, and protonation of AQ(-) water leads to PCET in the presence of water. A slower forward and backward electron- transfer rate is observed in the presence of D2O compared with that in H2O. These results provide further experimental support for a detailed understanding of the PCET process.

Hydrogen bond assisted photoinduced intramolecular electron transfer and proton coupled electron transfer in an ultrafast time domain using a ruthenium-anthraquinone dyad - Dey, Ananta; Dana, Jayanta; Aute, Sunil; Das, Amitava; Ghosh, Hirendra N. (Photochemical & Photobiological Sciences, 2019)
Quinones play a significant role as primary electron acceptors in the natural photosynthetic system of photosystem II, and their reduction is known to be facilitated by hydrogen-bond donors or protonation. In this study, a ruthenium(ii) polypyridyl complex 1 coupled to an anthraquinone (AQ) functionality through a rigid imidazole (Im) spacer has been synthesized to examine the effect of H-bonding on both the thermal and photoinduced electron transfer reactions. The anthraquinone moiety of complex 1 is fused to a benzi-imidazole system bearing C & xe001;(OMIDLINE)-M-AQ HORIZONTAL ELLIPSISHNIm based H-bonding at one side of the anthraquinone moiety so that intramolecular hydrogen bonding from the imidazole group to the nearby quinone carbonyl can occur. The hydrogen bond formation involving the semiquinone radical anion produced through the photoinduced reduction process in Ru-im-AQ and the imidazole proton in complex 1 resulted in a significant positive shift of one electron reduction potential of complex 1. The kinetics for the formation of the charge-separated states was explored by using femtosecond transient absorption spectroscopy. Hydrogen bonding between water and the reduced anthraquinone accounted for thermodynamic and kinetic stabilization of these charge-separated states. An attempt has been made to assess the relative importance of the driving force and solvent polarity, in the rates of photoinduced electron transfer in complex 1. The 490 nm transient absorption band of anthraquinone radical anions (AQ(-)) and a broad absorption in the 580-750 nm region having maxima at similar to 690 nm have been observed and this is attributed to the generation of a transient Ru3+-species of the corresponding complex 1. Addition of water entails an acceleration of electron transfer rates by a factor of 3.33. The system investigated may serve as a model for the mechanistic diversity of PCET reactions in general with water as a primary proton donor. Furthermore, our studies are relevant for understanding proton-coupled electron transfer (PCET) reactivity of electronically excited states at a fundamental level because changes in hydrogen-bonding strength accompanying changes in redox states may be regarded as a variant form of PCET.